Penerapan Metode K-Means Clustering Bagi Balita Penderita Stunting Di Kecamatan Loli Kabupaten Sumba Barat - Betharia Sonata Kaka (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The k-means clustering method is one of the data mining techniques that can be utilized for data grouping as a clustering process to determine the stunting status of toddlers, especially in the Loli District of West Sumba Regency. Data collection was done through direct observation at the Tanarara and Wee Karou Community Health Centers, with a total of 426 cases of stunted toddlers. The research results indicate that the application of the K-Means clustering method using Rapid Miner tools for the clustering of stunting patients in the Loli District in 2023 is divided into 3 clusters. Cluster 0 has the lowest level of stunting cases, Cluster 1 falls in the category of the highest stunting cases, and Cluster 2 is in the category of average stunting cases. Based on the research results, it can be concluded that the Soba Wawi and Bera Dolu Villages are in Cluster 1, with 77 and 66 cases of stunting patients, respectively.